Effects of balloon pulmonary angioplasty procedure on electrocardiographic parameters in patients with chronic thromboembolic pulmonary hypertension - KOL, AYHAN; KEPEZ, ALPER; ATAŞ, HALİL; MUTLU, BÜLENT (My University, 2023)
Aim: The aim of the present study was to evaluate the value of electrocardiography (ECG) in predicting post-operative hemodynamic improvement in patients with chronic thromboembolic pulmonary hypertension (CTEPH) undergoing balloon pulmonary angioplasty (BPA).Material and methods: A total of 32 patients were included in the study. During ECG analysis, parameters that have been suggested to be related to right ventricular hypertrophy and/or dilatation were evaluated. The sig-nificance of the change in each parameter obtained at the pre-BPA visit and at the scheduled control visit 6 months after BPA was tested. In addition to ECG analysis, data related to right heart catheterization (RHC) and echocardiography, B-type natriuretic peptide (BNP) levels and World Health Organization (WHO) functional classifications of all patients were also recorded. The relationship between the amount of possible change in ECG parameters and the amount of possible change in hemodynamic parameters was investigated.Results: The Daniel score, which has been suggested to have prognostic value in acute pulmonary embolism, decreased from 8.22 +/- 5.68 to 6.56 +/- 5.55 after the BPA procedure (p: 0.035). Among all parameters studied, only T wave height (V2 t) in V2 derivation changed significantly from-0.77 +/- 2.39 to 1.27 +/- 2.58 mm (p: 0.036). The amount of change in V2 T was found to significantly correlate with the amount of change in systolic right ventricular pressure, mean pulmonary artery pressure, pulmonary vascular resistance, and systemic vascular resistance.Conclusion: Postprocedural T wave changes in lead V2 might serve as a marker of hemodynamic improvement in patients with CTEPH who undergo BPA.
Keywords: Tıp; Dahili Tıp Bilimleri; Kardiyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Cardiovascular; Health Sciences; KALP VE KALP DAMAR SİSTEMLERİ; Klinik Tıp; Klinik Tıp (MED); CARDIAC & CARDIOVASCULAR SYSTEMS; CLINICAL MEDICINE; Clinical Medicine (MED); Kardiyoloji ve Kardiyovasküler Tıp; Cardiology and Cardiovascular Medicine; Chronic thromboembolic pulmonary; hypertension; Pulmonary balloon angioplasty; ECG; Right heart failure; HYPERTROPHY; ASSOCIATION; Chronic thromboembolic pulmonary; hypertension; Pulmonary balloon angioplasty; Right heart failure; EGG